Start-up Speed Anomaly Detection Method of Urban Rail Train - YANG Wenrui; XIAO Zhijun (机车电传动)
Aiming to the uncertainty of existing urban rail train start-up speed anomaly judged by human, a train start-up speed anomaly detection method was proposed based on declination threshold of acceleration ratio and its standard deviation. Feasibility and implementation steps of the method were researched. With high certainty and reliability comparing to the human judgment, this method could be used to detect relevant parts hidden faults of train start-up speed variation, which improved the safety of train operation effectively in a certain extent.